2012
DOI: 10.1016/j.physc.2012.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of stripe-ordered high Tc cuprates

Abstract: Transport measurements provide important characterizations of the nature of stripe order in the cuprates. Initial studies of systems such as La 1.6−x Nd 0.4 Sr x CuO 4 demonstrated the strong anisotropy between inplane and c-axis resistivities, but also suggested that stripe order results in a tendency towards insulating behavior within the planes at low temperature. More recent work on La 2−x Ba x CuO 4 with x = 1/8 has revealed the occurrence of quasi-two-dimensional superconductivity that onsets with spin-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…1 CDW in cuprate superconductors were first observed in lanthanum based compounds, [2][3][4] such as La 2−x Ba x CuO 4 (LBCO) around 1/8 hole-doping. 2,[4][5][6][7][8][9][10][11][12] In these La-based cuprates, spin correlations were also found to synchronize with the CDW modulation to form static "stripes" 2 of interlocked CDW and spin density waves (SDW) at a certain temperature below the ordering temperature of the CDW (see Fig. 1).…”
Section: Significance Statementmentioning
confidence: 99%
“…1 CDW in cuprate superconductors were first observed in lanthanum based compounds, [2][3][4] such as La 2−x Ba x CuO 4 (LBCO) around 1/8 hole-doping. 2,[4][5][6][7][8][9][10][11][12] In these La-based cuprates, spin correlations were also found to synchronize with the CDW modulation to form static "stripes" 2 of interlocked CDW and spin density waves (SDW) at a certain temperature below the ordering temperature of the CDW (see Fig. 1).…”
Section: Significance Statementmentioning
confidence: 99%
“…Because of the crystal symmetry, the orientation of the stripes rotates 90 • from one layer to the next. The occurrence of maximum stripe order corresponds to a strong suppression of the bulk T c at p ≈ 1 8 [54,57], suggesting that stripe order competes with superconductivity; however, recent studies have demonstrated that 2D superconductivity can coexist with stripe order [58]. It now appears that superconducting order can intertwine with stripe order [59].…”
Section: Application To Cuprate Superconductorsmentioning
confidence: 99%
“…22 For x = 0.115 at 7 K, the JPR appears near the renormalized superconducting plasma frequency ω′ p = 6.7 cm −1 (200 GHz). The unscreened plasma frequency is given by ω p = ω′ p εitalic∟εitalic∟30 giving a superfluid density ρ o ≡ ω p 2 = 1.3 × 10 3 cm −2 (This is taken to be very near the superfluid density at T = 0 K.) The conductivity just above T c = 13 K is taken as σ dc ∼ 0.8 Ω −1 ⋅cm −1 , estimated from transport measurements on a similar doping of x = 0.11 (24). As seen in Fig.…”
mentioning
confidence: 99%
“…The unscreened plasma frequency is given by ωp = ω'p ( ) giving a superfluid density ρo ≡ ωp 2 = 1.3 x 10 3 cm -2 (This is taken to be very near the superfluid density at T = 0 K). The conductivity just above Tc = 13 K is taken as σdc ~ 0.8 Ω -1 cm -1 , estimated from transport measurements on a similar doping of x = 0.11 24 . As seen in Fig.…”
mentioning
confidence: 99%